THE INFLUENCE OF TEACHING METHODS ON THE INTEREST IN LEARNING ARABIC AMONG GRADE IX B FEMALE STUDENTS: A STUDY AT MUHAMMADIYAH JUNIOR HIGH SCHOOL PURWODADI, PURWODADI CITY - Firdaus, Hanifah Nur; Putra, Sudarmadi (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to analyze the influence of teaching methods on students' interest in learning Arabic at SMP Muhammadiyah Purwodadi. Using a quantitative descriptive approach, data were collected through observation, interviews, and documentation involving female students of class IX B. The findings indicate that students initially show high interest in Arabic, but their enthusiasm declines due to monotonous teaching methods. Factors affecting their interest include internal motivation, attention during learning, and the teacher's attitude and teaching materials. Students expressed a desire for more interactive methods, such as using songs, animated videos, and games, which they believe would enhance engagement. The study concludes that creative and varied teaching methods significantly impact students' interest in learning Arabic. Teachers play a crucial role in fostering this interest by adopting innovative approaches tailored to students' preferences